The Relationship Between Dietary Patterns and Physical Activity with Total Cholesterol Levels in Middle-Aged Adults in Petapahan Village, Deli Serdang Regency, 2025 - Pratiwi, Marta Aditya; Ahmad Hafizullah Ritonga; Raisha Octavariny; Tati Murni (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Cholesterol is essential for the formation of cell membranes, bile salts, hormones, and vitamin D, as well as serving as an energy source. Reduced physical activity in middle-aged adults can decrease organ function and increase the risk of metabolic disorders, while a diet high in saturated fat and low in fiber may elevate blood cholesterol levels. This study aimed to determine the relationship between dietary patterns and physical activity with total cholesterol levels in middle-aged adults in Petapahan Village, Deli Serdang Regency. Using a quantitative cross-sectional design with 47 respondents, data were collected through interviews, the Food Frequency Questionnaire (FFQ), a physical activity questionnaire, and cholesterol meter measurements, and analyzed using the Spearman correlation test. The results showed that 64% of respondents frequently consumed certain foods, 57% had light physical activity, and 36% had high cholesterol levels. Statistical analysis revealed a significant relationship between dietary patterns and physical activity with total cholesterol levels (p = 0.000), indicating that both factors are associated with cholesterol levels in middle-aged adults.